The bridge (translated by Mac Linscott Ricketts) - Eliade, Mircea (Archaeus, 2011)
One of Eliade’s more difficult novellas to decipher, it consists of a series of seemingly unconnected plots involving a variety of characters, whose bizarre adventures gradually become more interwoven as the work progresses. The main theme is the unrecognizability of miracle, or the camouflage of mystery in ordinary reality. Not a fantastic story, it belongs more properly to the genre of mystery or philosophical narrative.